Metabolic Implications of Elevated Neutrophil Extracellular Traps in Polycystic Ovary Syndrome: A Focus on Hepatic Glycolysis - Siyu Lin; Yushan Li; Wei Liu; Yanzhi Du; Tao Tao (Biomolecules)
Background: Polycystic ovary syndrome (PCOS) is a leading cause of infertility but also a metabolic disorder, frequently associated with obesity, insulin resistance, and diabetes. However, its etiology remains inadequately understood. Recent studies have increasingly implicated neutrophil extracellular traps (NETs) in the pathogenesis of metabolic diseases. Methods: Serum and follicular fluid samples were collected from patients with PCOS and control populations to assess NETs levels. The effects of NETs were investigated using DNase I to reduce NETs in dehydroepiandrosterone sulfate (DHEAS)-induced PCOS rats. Metabolic differences were further analyzed by untargeted metabolomics, and in vitro studies were conducted using primary bone marrow-derived neutrophils and normal mouse liver cell lines. Results: Markers of NETs in both the serum and follicular fluid of patients with PCOS were significantly higher than those in the control group. PCOS rats treated with DNase I exhibited significant improvements in glucose metabolism. Untargeted metabolomics analysis of liver tissue from these rats revealed alterations in the glycolysis pathway. Subsequent in vitro experiments demonstrated that treatment with NETs-conditioned medium (NETs CM) led to reduced insulin sensitivity, glucose uptake, and glucose utilization in liver cells, accompanied by varying degrees of decline in the transcription, translation, and function of glycolysis pathway proteins. Conclusions: NETs may be involved in the regulation of insulin resistance pathogenesis in PCOS by downregulating glycolytic pathways in the liver. Our study offers a novel strategy for insulin resistance intervention in PCOS.